Education of How-to-Use Peak Flow Meter and Following up via SMS on Asthma Self-Management - Anooshirvan Kazemnejad; Mitra Zolfaghari; Najmeh Piroozmand; Shadan Pedram Razi; Shahram Firoozbakhsh (Tehran University of Medical Sciences, 2012)
Background & Aim: Asthma is one of the most prevalent chronic diseases worldwide. About 6.5 million people suffer from asthma in Iran. The Effective strategy to control asthma is related to education. The self-management has a major role in the standard education program. This study aimed to assess the effect of education on using peak flow meter and follow up via SMS on asthma self management.Methods & Materials: This study was a quasi-experimental controlled clinical trial. The samples included 98 patients, suffering from asthma referred to the pulmonary clinic in Imam Khomeini and Shariati hospitals. Patients were selected using convenient sampling method and were randomly assigned into the experiment (n=47) and control (n=51) groups through blocking method. Two educational sessions were held in the experiment group about how-to-use peak flow meter. Accordingly, the patients in the experiment group sent their peak flow rates via SMS to the researcher within 12 weeks. The researchers provided feedback to the patients about their asthma control via phone, weekly. Patients in the control group did not receive any education. Data were collected using the Asthma Control Test before and three months after the intervention. Data were analyzed using the statistical tests of Chi-square, Mann-Whitney, Independent t-test and Kolmogorov-Smirnov.Results: There was a significant statistical difference between the two groups of experiment and control in terms of asthma control (P=0.002).Conclusion: The education using peak flow meter and following up via SMS promotes asthma self-management. With regard to the significant role of nurses in patient education, educating patients with asthma by nurses is recommended at the Iranian Society of Asthma and Allergies clinics and medical centers.